2018
DOI: 10.3390/ijms19103076
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein (AMPK) in Pathophysiology of Pregnancy Complications

Abstract: Although the global maternal mortality ratio has been consistently reduced over time, in 2015, there were still 303,000 maternal deaths throughout the world, of which 99% occurred in developing countries. Understanding pathophysiology of pregnancy complications contributes to the proper prenatal care for the reduction of prenatal, perinatal and neonatal mortality and morbidity ratio. In this review, we focus on AMP-activated protein kinase (AMPK) as a regulator of pregnancy complications. AMPK is a serine/thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 82 publications
(106 reference statements)
2
37
0
Order By: Relevance
“…Several lines of evidence advocate the use of ER stressors as potential drugs for the treatment of both B-ALL and T-ALL. Earlier studies focused on how the AMP-activated kinase (AMPK) activator 5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR [144]) in combination with either methotrexate or 2-deoxy-D-glucose (2-DG, a sugar analog that inhibits both glycolysis and N-linked glycosylation [145]), induced a prolonged ER stress in B-ALL cells, thereby leading to proapoptotic UPR via IRE1α, GRP78, phosphorylated eIF2α, and CHOP [146]. Similar results were reported with the AMPK activator metformin that led to UPR-mediated apoptosis via upregulation of IRE1α and CHOP [138].…”
Section: Therapeutic Strategies For B-all and T-allmentioning
confidence: 99%
“…Several lines of evidence advocate the use of ER stressors as potential drugs for the treatment of both B-ALL and T-ALL. Earlier studies focused on how the AMP-activated kinase (AMPK) activator 5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR [144]) in combination with either methotrexate or 2-deoxy-D-glucose (2-DG, a sugar analog that inhibits both glycolysis and N-linked glycosylation [145]), induced a prolonged ER stress in B-ALL cells, thereby leading to proapoptotic UPR via IRE1α, GRP78, phosphorylated eIF2α, and CHOP [146]. Similar results were reported with the AMPK activator metformin that led to UPR-mediated apoptosis via upregulation of IRE1α and CHOP [138].…”
Section: Therapeutic Strategies For B-all and T-allmentioning
confidence: 99%
“…Studies of peripheral macrophages show that activation of the JAK2/STAT3 signaling pathway can induce the expression of HMGB1, which promotes the release of cytokines such as TNF-α and IL-6, thus induces the inflammatory reaction. 84 It was found that curcumin supplementation suppresses the phosphorylation levels of the JAK2 in IUGR rats. 57 Furthermore, curcumin can attenuate hepatic oxidative stress by activating the NRF2 pathway.…”
Section: Protective Effect Of Curcumin Against Intrauterine Growth mentioning
confidence: 99%
“…84 In a stress state, ATP consumption causes AMPK activation that leads to increased concentration of cellular ATP. 84 AMPK activation has been found to alleviate maternal diabetic disease and consequently normalize fetal growth. 84,99,105 Of note, AMPK activation by curcumin was found to alleviate GD, which is associated with decreased expression of HDAC4 (histone deacetylases-4) and glucose-6-phosphatase (G6Pase).…”
Section: Gestational Diabetes and Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented the role of FA in suppressing endothelial oxidative stress and placental inflammatory response, which in turn alleviates the disease pathology [15,16]. Moreover, AMPK activation is not only necessary for the placental differentiation and growth but also regulating the inflammatory response in the placenta [45]. Intriguingly, both antiviral and anti-inflammatory effects of FA may play a role in limiting ZIKV transmission through maternal-fetal interface.…”
Section: Plos Pathogensmentioning
confidence: 99%